Living in deprived neighbourhoods in Scotland. Occupational mobility and neighbourhood effects. - David Manley; Maarten Van Ham (European Regional Science Association (ERSA), 2010)
The idea that living in a deprived neighbourhood negatively affects the occupational mobility of residents has been embraced enthusiastically by many policy makers and academics. As a result, area based initiatives are now widely used to improve an individual's life course through the diversification of the neighbourhood in which they live. However, these area based initiatives have received increasing criticism from academics stating that there is no solid evidence base that neighbourhood effects really exist. One of the main problems is that many studies use cross-sectional data which does not allow the separation of cause and effect. We use longitudinal data from the Scottish Longitudinal Study (SLS) to investigate the influence of neighbourhood context on employment outcomes. The SLS allows us to follow individuals between 1991 and 2001, using linked records from both Censuses. Using this data we examine whether, for employed individuals, living in a deprived neighbourhood reduces occupational mobility using ISEI scores; for individuals out of work, we examine whether living in a deprived neighbourhood reduces their chances of obtaining work. Using regression models, we control for a range of individual and household characteristics. All other things being equal, those individuals living in more deprived communities should experience significant negative effects accrued from their neighbourhood if the neighbourhood effects thesis is to be confirmed.
Keywords: 330; Tenure Mix; Deprivation; Neighbourhood Effects; Occupational Mobility; Longitudinal Data; Scotland